Analisis kepatuhan wajib pajak UMKM di Kantor Pelayanan Pajak Pratama Manado - Lolowang, Eunike; Sondakh , Jullie J.; Mintalangi, Syermi S. E. (Riset Akuntansi dan Portofolio Investasi, 2024)
Taxpayer compliance is an important element that must be considered, because if taxpayers do not comply and fulfill their tax obligations it will have an adverse impact on the state, because if taxpayers do not fulfill their tax obligations, state treasury revenues will decrease, because tax is one of the the largest source of revenue for the country. The freedom given to taxpayers in calculating, depositing and reporting their own taxes owed is expected to maximize the growth in the level of compliance of MSME taxpayers. The aim of this research is to determine the level of compliance of MSME taxpayers at KPP Pratama Manado in 2022-2023. The research method used is descriptive qualitative by analyzing, describing and explaining the findings derived from data collected through interviews at KPP Pratama Manado. The research results show that the compliance level of MSME Taxpayers at KPP Pratama Manado in the 2021-2023 period is categorized as low with a percentage of 6.69% in 2021 and 9.50% in 2022 and 5.83% in 2023, and the percentage ratio of the level of compliance with Annual SPT reporting based on the number of Taxpayers with Active NPWP status within a period of 3 years, namely 2021-2022, is categorized into a fairly standard score with a percentage of 79.58% in 2021 and 76.85% in 2022 and in 2023 it is categorized as a low standard score with a percentage of 33.78%.